2004
DOI: 10.1097/01.nmd.0000126729.08179.07
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Depression Among Ethiopian Immigrants and Refugees in Toronto

Abstract: The purpose of this study was to determine the occurrence of and risk factors for depressive disorder in a random sample of 342 Ethiopian immigrants and refugees in Toronto. The Composite International Diagnostic Interview questionnaire was used to measure depression. The results suggested a lifetime prevalence of depression among Ethiopian immigrants and refugees of 9.8%, which was slightly higher than the lifetime prevalence rate in the Ontario population (7.3%). However, the rate among Ethiopian immigrants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
5
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(122 citation statements)
references
References 33 publications
9
106
5
2
Order By: Relevance
“…Each item was coded on a Likert scale, ranging from 0 (absence of the symptom) to 3 (consistent/daily experience of symptom). CES-D has been used in community-based and clinical samples of individuals with various health conditions including physical or psychiatric illness and disability, including adults with HIV [13,38,39] and immigrants [27,40]. To date, there has yet to be a validated measure of either depressive or HIV symptom severity that effectively distinguishes the somatic symptoms that are characteristic of both conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Each item was coded on a Likert scale, ranging from 0 (absence of the symptom) to 3 (consistent/daily experience of symptom). CES-D has been used in community-based and clinical samples of individuals with various health conditions including physical or psychiatric illness and disability, including adults with HIV [13,38,39] and immigrants [27,40]. To date, there has yet to be a validated measure of either depressive or HIV symptom severity that effectively distinguishes the somatic symptoms that are characteristic of both conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Children and especially adolescents experience discrimination and prejudice from their peers in school and social settings, with more intense expression of what is more subtle amongst adult counterparts. Discrimination is increasingly recognized as an adverse mental health risk (Finch, Kolody, & Vega, 2000).…”
Section: Post-migration Stressorsmentioning
confidence: 99%
“…For instance, the prevalence of depression disorder was 20% among labor migrants [33], 14% among Haitian immigrant students [34], 16.7% of trafficked women [35], 55% of trafficked and sexually exploited females [36] and 20% of migrants in Sweden [37]. Also, Haile et al research results suggested that a lifetime prevalence of depression disorder among Ethiopian immigrants in Toronto was 9.8%, which was slightly higher than the lifetime prevalence in the Ontario population (7.3%).…”
Section: Introductionmentioning
confidence: 99%